(untitled) - Hersh, Seymour M. (New York, 1970)
A report on the slaughter of 102 South Vietnamese civilians in 1968, and the investigation into the actions of the American soldiers who were involved in this mass murder
Keywords: Thảm sát Mỹ Lai, Việt Nam, 1968,My Lai massacre, Vietnam, 1968